Power and purpose : U.S. policy toward Russia after the Cold War - Goldgeier, James M. (Brookings Institution Press, 2003)
"This book traces the evolution of American foreign policy toward the Soviet Union, and later Russia, during the tumultuous and uncertain period following the end of the cold war. It examines how American policymakers - particularly in the executive branch - coped with the opportunities and challenges presented by the new Russia." "Understanding how three U.S. administrators dealt with critical policy questions is vital in assessing not only America's Russia policy, but also efforts that might help to transform and integrate other former adversaries in the future."--Jacket